EDUKASI KESEHATAN SADARI UNTUK MENCEGAH KANKER PAYUDARA PADA SISWI SMAN 4 KOTA PADANG - Syafrawati Syafrawati; Ayulia Fardila Sari ZA (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2021)
Data from the Padang City Health Office in 2017 showed that there were 142 women diagnosed with breast cancer in the city of Padang. There are 25.4% of patients with breast cancer in the working area of the Lubuk Begalung Health Center. Community service activities at FKM Unand are carried out with BSE health promotion efforts to prevent breast cancer in SMAN 4 Padang City students. SMAN 4 Padang is one of the schools that has the most students with the average student being part of the population of Lubuk Begalung District. The target of the service output is to increase students' knowledge about breast cancer and students' skills in BSE as an effort to detect breast cancer early. The implementation method is carried out by counseling about breast cancer prevention through BSE activities. The result of the average pretest score of knowledge level is 5.2 with a standard deviation of 1.70. While the results of the post-test average knowledge level was 7 with a standard deviation of 1.51. The statistical test results obtained a p value of 0.000, so it can be concluded that there is a significant difference between the level of knowledge of pre-test and post-test education about BSE in students of SMAN 4 Padang. It is hoped that similar activities can be carried out at other schools in the city of Padang considering that from the results of questions and answers with students, the socialization carried out is an effort to increase students' knowledge regarding breast cancer prevention.